Severe iatrogenic bradycardia related to the combined use of beta-blocking agents and sodium channel blockers - Kawabata M (Dove Medical Press, 2015)
Mihoko Kawabata,1 Yasuhiro Yokoyama,1 Takeshi Sasaki,1 Susumu Tao,1 Kensuke Ihara,1 Yasuhiro Shirai,1 Tetsuo Sasano,2 Masahiko Goya,1 Tetsushi Furukawa,3 Mitsuaki Isobe,4 Kenzo Hirao1 1Heart Rhythm Center, Tokyo Medical and Dental University, Tokyo, Japan; 2Department of Biofunctional Informatics, Graduate School of Health Care Sciences, Tokyo Medical and Dental University, Tokyo, Japan; 3Department of Bio-informational Pharmacology, Medical Research Institute, Tokyo Medical and Dental University, Tokyo, Japan; 4Department of Cardiovascular Medicine, Tokyo Medical and Dental University, Tokyo, Japan Purpose: Drug-induced bradycardia is common during antiarrhythmic therapy; the major culprits are beta-blockers. However, whether other antiarrhythmic drugs are also a significant cause of this, alone or in combination with beta-blockers, is not well known. Methods: We retrospectively investigated the records of all patients hospitalized at our institution for drug-related bradycardia from the years 2004 to 2012. Patients with cardiac disease and electrolytic or hormonal abnormalities that could cause bradyarrhythmias were excluded. Results: Eight patients were identified (mean age, 79±5 years; range, 71–85 years; 6 women). Three patients were taking only beta-blockers (hereafter referred to as the BB group), while five patients were on both beta-blockers and Na channel blockers (hereafter referred to as the BB + Na group). Heart rates ranged from 20~49 beats/minute on arrival. The initial electrocardiogram showed sinus bradycardia (n=6) or sinus arrest with escape beats (n=2). QRS duration was 80–100 ms. The clinical presentation of the BB + Na group was considerably worse than that of the BB group, and included cardiogenic shock and heart failure. Four of the BB + Na patients had been on their medications for over 300 days. The BB group recovered solely with drug discontinuation, while 4 of the 5 patients in the BB + Na group needed additional treatments, such as intravenous administration of atropine or adrenergic agonist and temporary pacing. Bradycardia did not recur during follow-up (median, 687 days). Conclusion: Although wide QRS ventricular tachyarrhythmia is a better known proarrhythmic effect of Na channel blockers, life-threatening bradycardia may also occur in combination with beta-blockers in the elderly, even months after the start of medication, and at plasma concentrations that do not prolong QRS width. Keywords: proarrhythmia, elderly, QRS duration